Interdependency, Competition, and the Distribution of Firm and Industry Profits - Lenox, Michael J.; Rockart, Scott F.; Lewin, Arie Y. (Management Science, 2006)
Coordination of interdependencies among firms’ productive activities has been advanced as a promising explanation for sustained heterogeneity in capabilities among firms. In this paper, we extend this line of research to determine the industry structures and patterns of expected firm profits for the case when difficulty optimizing interdependent activities does, in fact, generate and sustain capability heterogeneity among firms. We combine a widely used agent-based model where firms search to discover sets of activities that complement one another (reducing overall costs or raising product quality) with traditional economic models of competition among profit-maximizing firms. The agent-based model produces a distribution of performance (interpreted as variable cost or product quality) among firms and the competition models determine resulting industry outcomes including patterns of entry, exit, and profits. The integration of economic models of competition among firms with an agent-based model of search for improvement by firms reveals a rich relationship between interdependencies in production functions and industry structure, firm profits, and industry average profitability.